Accelerating Progress on Women’s and Children’s Health - Presern, Carole (World Health Organization, 2015)
Countries have made substantial progress towards Millennium Development Goals (MDGs) 4 and 5 – to reduce child mortality and improve maternal health. Since 1990, both maternal and child mortality have been reduced by 50% worldwide and access to reproductive health services has improved. However, progress overall is insufficient and uneven. Understanding what works, and how these lessons apply across geographic and socio-political borders, could inform strategies for the MDGs and the post-2015 sustainable development agenda. An article in this month’s Bulletin synthesizes evidence from studies on success factors for women’s and children’s health in low- and middle-income countries that achieved accelerated progress (fast-track countries).